Armazenamento e viabilidade de sementes de catanduva (Piptadenia moniliformis Benth). - Benedito, Clarisse Pereira (Universidade Federal Rural do Semi-Árido, 2010)
This study aimed to evaluate the viability of catanduva seeds of stored for two hundred and ten days in controlled environmental and uncontrolled environmental conditions (laboratory room) they were stored in plastic bags, paper bags and glass container. The experimental design was completely randomized in a sub-divided plot, where the main plot was the storage conditions (laboratory and controlled environment) and sub-plots consisting of packaging (plastic bag, paper bag and glass container) and sub-plots consisting of storage times (0, 30, 60, 90, 120, 150, 180 and 210 days). The tests were carried out in laboratory and greenhouse. In the laboratory the percentage of germination and rate of germination speed was evaluated every 10 days. In the greenhouse seedling emergence, seedling height, root length and dry weight of seedlings was evaluated every 30 days. The viability of catanduva seeds decreased for being stored for a period of 210 days. The catanduva seeds (Piptadenia moniliformis Benth) can be packed either in glass container or plastic bags without loss of their physiological potential, and the controlled environment is the most appropriate for the storage of those seeds.
Storage and viability of catanduva seeds (Piptadenia moniliformis Benth)
Keywords: Piptadenia moniliformis; Armazenamento; Viabilidade; Piptadenia moniliformis Benth; Storage; Viability; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA